The Role of Educational Technology in Enhancing Student Motivation in the Digital Era - Firmansyah, Ricky (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2025)
This study aims to analyze the role of educational technology in enhancing student motivation in the digital era. In the context of education increasingly reliant on technology, it is essential to understand how technology influences student motivation in the learning process. This research employs a literature review method with a qualitative approach, examining various recent studies and literature related to educational technology and student motivation. The analysis results show that educational technology, such as e-learning, interactive learning applications, and gamification, can enhance student motivation by providing flexibility, active engagement, and constructive feedback. However, factors such as teacher skills, accessibility to technology, and the design of learning that aligns with student characteristics are key elements influencing the effectiveness of technology in improving learning motivation. This study recommends the importance of teacher training and strengthening technological infrastructure to maximize the potential of educational technology in improving student motivation and learning outcomes.